Design and Development of SpO2, Bpm, and Body Temperature for Monitoring Patient Conditions in IOT-Based Special Isolation Rooms - Purwitosari, Dyah; Irianto, Bambang Guruh; Triwiyanto, Triwiyanto; Huynh, Phuoc-Hai (Jurnal Teknokes, 2023)
The utilization of batteries as the primary power source in portable equipment systems presents certain drawbacks, primarily concerning the need for constant monitoring of battery power to ensure uninterrupted system functionality. Therefore, this study aims to address the battery power efficiency analysis to evaluate the viability of portable systems. The research endeavors to develop a portable measurement system capable of monitoring SPO2 (blood oxygen saturation), BPM (beats per minute), and body temperature in a specialized isolation treatment room. The proposed system is designed to assess the health conditions of patients afflicted with infectious diseases by measuring their heart rate, body temperature, and oxygen saturation. The devised measurement system incorporates a 2200mAH battery to power the IC TTGO ESP32, which manages data and displays measurement results. Additionally, the system integrates the MAX30102 sensor to measure oxygen saturation and heart rate, along with the MCP9808 sensor to monitor body temperature. To ensure its accuracy, the designed device underwent rigorous testing on respondents aged 25-40 years. The sensors were placed on the fingertip, and the resulting measurements were compared against those obtained from a standardized and calibrated device. The analysis of the measurement results exhibited a commendable ±5% error margin, indicating the feasibility of the proposed device for practical usage. Moreover, the study scrutinized the efficiency of battery power utilization in two distinct modes: normal mode and save mode. In the normal mode, the device consumed a current of 154.9 mA, while the save mode, which involved deactivating the LCD TTGO ESP32, required a current of 126.7 mA. The findings demonstrated that the device could operate for approximately ±14 hours in normal mode and up to ±17 hours in save mode before the battery needed recharging. The proposed design presents an effective approach for evaluating power efficiency in various device modes. Additionally, it empowers users by providing insights into the regular battery charging times, thus enabling them to determine the duration for which the device can be utilized to monitor patients. This knowledge proves invaluable for healthcare practitioners, as they can ensure uninterrupted monitoring while managing battery charging schedules effectively. Overall, this portable measurement system offers a promising solution for enhancing patient care and disease management in isolation treatment rooms.